Trade relations of the Safavid state with foreign countries - Kake Amin, Dara Tofiyq (Humanities Journal of University of Zakho, 2018)
Trade is one of the most important economic activities, where the consumer gets to life through a point of communication between the producer and the consumer. Trade is divided into internal and external trade, where the internal trader’s responsibility is to deliver and provide products and services within the geographical boundaries of the state. Foreign trade is the process of exchanging national economic products outside the country’s geographical borders, as well as the transfer of ownership of products and resources to one another through the import and export process. Therefore, trade is the important areas of life, which have become important factors that affected the economy (Iran) in a record period in the Safavid era, which led to the expansion and development of trade relations with neighboring countries abroad, and in order to recognize the importance of this aspect, this research Shows the importance of trade and its impact on political treaties of that era. This research is divided into an introduction with three main sections, the first deals with domestic and foreign trade, while the second section highlights the attention on trade routes, either the third and last section was for the purpose of studying the commercial relations of Safavid with other Nations, which include the (Ottoman, The Portuguese, British, Dutch, French, and Russians).